The long call [large type] - Cleeves, Ann (Cleeves, Ann. Two rivers series, 2019)
In North Devon, where two rivers converge and run into the sea, Detective Matthew Venn stands outside the church as his father's funeral takes place. Once loved and cherished, the day Matthew left the strict evangelical community he grew up in, he lost his family too. Now, as he turns and walks away again, he receives a call from one of his team. A body has been found on the beach nearby: a man with a tattoo of an albatross on his neck, stabbed to death. The case calls Matthew back into the community he thought he had left behind, as deadly secrets hidden at its heart are revealed, and his past and present collide. An astonishing new novel told with compassion and searing insight, The Long Call will captivate fans of Vera and Shetland, as well as new readers.